Auditory perception in people with autism spectrum disorders - Đoković, Sanja; Gligorović, Milica; Ostojić-Zeljković, Sanja (Specijalna edukacija i rehabilitacija, 2022)
Introduction. The occurrence of atypical reactions to auditory sensory stimuli is observed in people with autism spectrum disorders (ASD) at an early age. Objective. The goal of this review was to analyze behavioural and electrophysiological examinations of auditory perception in people with ASD. Methods. The findings are organized according to the applied methodology and stimuli used in assessing auditory perception. Results. When compared to the typical population, identification and discrimination of isolated acoustic characteristics are mostly preserved or advanced in people with ASD, both for complex tones and spoken stimuli. The leading theories regarding auditory functioning of people with ASD indicate that peripheral (local) processing of sound details is preserved or advanced compared to the typical population and that difficulties arise in integrating locally analyzed information into a meaningful whole (global processing). The difference between these theories is that the Weak Central Coherence theory insists on a definite presence of deficiencies in global processing, whereas the Perceptual Functioning theory is not as exclusionary and indicates that the inconsistency in global processing can be present but is not requisite. Conclusion. It may be concluded that auditory perception and the processing of tone height are preserved or enhanced in people with ADS regardless of the type of the auditory stimulus. This may be explained by the increase of the auditory capacity for information processing, which is useful in some cases. However, in other cases, the same increased capacity results in processing unnecessary information, thereby increasing susceptibility to distraction.
Keywords: auditory perception; autism spectrum disorders; behavioural indicators; electrophysiological indicators